Protection of pregnant women at work in Switzerland: practices, obstacles and resources. A mixed-methods study protocol. Issue 6 (14th June 2018) - Krief, Peggy; Zellweger, Alessia; Politis Mercier, Maria-Pia; Danuser, Brigitta; Wild, Pascal; Zenoni, Michela; Probst, Isabelle
Abstract : Introduction: Like most industrialised countries, Switzerland has introduced legislation to protect the health of pregnant workers and their unborn children from workplace exposure. This legislation provides for a risk assessment, adaptations to workplaces and, if the danger is not eliminated, preventive leave (prescribed by a gynaecologist). This study's first objective is to analyse the degree to which companies, gynaecologists and midwives implement the law. Its second objective is to understand the obstacles and resources of this implementation, with a focus on how relevant stakeholders perceive protective measures and their involvement with them. Methods and analysis: Data will be collected using mixed methods: (1) online questionnaires for gynaecologists and midwives; telephone questionnaires with company human resources (HR) managers in the healthcare and food production sectors; (2a) case studies of 6–8 companies in each sector, including interviews with stakeholders such as women workers, HR managers and occupational health physicians; (2b) two focus groups, one involving occupational physicians and hygienists, one involving labour inspectors. Quantitative data will be analysed statistically using STATA software V.15. Qualitative data will be transcribed and thematically analysed using MaxQDA software. Ethics and dissemination: The Human Research Ethics Committee of the Canton Vaud (CER-VD) has certified that this research study protocol falls outside of the field of application of the Swiss Federal Act on Research Involving Humans. The publications and recommendations resulting from this study will form the starting point for future improvements to the protection of pregnant women at work and their unborn children. This study started in February 2017 and will continue until January 2020.